Na(+)/K(+)-ATPase inhibition by cisplatin and consequences for cisplatin nephrotoxicity - Kubala, Martin; Geletičová, Jaroslava; Huličiak, Miroslav; Zatloukalová, Martina; Vacek, Jaroslav; Šebela, Marek (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
AIMS: Cisplatin is a widely used chemotherapeutic. However, it is associated with numerous adverse effects. The aim of our study was examination of cisplatin interaction with Na(+)/K(+)-ATPase (NKA, the sodium pump). This enzyme is of crucial importance for all animal cells and particularly for the kidney, which is frequently damaged during chemotherapy. METHODS: The entire NKA was isolated from porcine kidney. Its large cytoplasmic segment connecting transmembrane helices 4 and 5 (C45), was heterologously expressed in E.coli (wild-type or C367S mutant). The ATPase activity was evaluated according to the inorganic phosphate production and the interaction of isolated C45 with cisplatin was studied using chronopotentiometry and mass spectrometry. RESULTS: Our experiments revealed that cisplatin can inhibit NKA. The finding that other platinum-based drugs with a low nephrotoxicity, carboplatin and oxaliplatin, did not inhibit NKA, suggested that NKA/cisplatin interaction is an important factor in cisplatin adverse effects. The inhibitory effect of cisplatin could be prevented by preincubation of the enzyme with reduced glutathione or DTT. Using chronopotentiometry and mass spectrometry, we found that cisplatin is bound to C45. However, our mutagenesis experiment did not confirm that the suggested Cys367 could be the binding site for cisplatin. CONCLUSION: Unintended interactions of drugs present serious limitations to treatment success. Although a large number of membrane pumps have been identified as potential targets of cisplatin, vis-a-vis nephrotoxicity, NKA inhibition seems to be of crucial importance. Experiments with isolated large cytoplasmic segment C45 revealed that it is the main target of cisplatin on NKA and that the reaction with cysteine residues plays an important role in cisplatin/NKA interactions. However, further experiments must be performed to identify the interacting amino acid residues more precisely.
Keywords: prasata; Swine; Sodium-Potassium-Exchanging ATPase; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Cisplatin; Antineoplastic Agents; ledviny; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; zvířata; Animals; sodíko-draslíková ATPasa; protinádorové látky; cisplatina; Kidney